Ecological And Educational Function Of Expositional Parks (Journal of Architectural Design, 2024)
This article delves into the multifaceted role and importance of parks as essential green spaces that offer substantial environmental and social benefits. Parks are highlighted as vital areas for recreational activities, providing a natural retreat within urban settings, and as educational resources, fostering environmental awareness and learning. The study underscores how parks contribute to the well-being of urban populations by offering spaces for physical activities, relaxation, and social interaction. Moreover, in many countries, prominent parks are integral to the cultural life of cities, hosting events, and festivals that enrich the community's cultural experience. These green spaces are instrumental in shaping eco-friendly urban environments, promoting biodiversity, and mitigating urban heat island effects. Furthermore, parks are shown to have significant economic implications, enhancing property values, attracting tourism, and stimulating local economies. The article concludes by asserting that the strategic development and maintenance of parks are key to fostering sustainable urban growth and improving the overall quality of life in cities